Structural studies of PfEMP1 bound to human cluster of differentiation 36 and of an unusual human antibody - Hsieh, F (2017)
In Plasmodium falciparum-infected humans, parasites escape from splenic clearance and cause severe or chronic symptoms partly through the action of the variable surface antigens expressed on the surfaces of infected erythrocytes, called P. falciparum erythrocyte membrane protein 1 (PfEMP1). PfEMP1 that interact with human Cluster of Differentiation 36 (CD36) receptor mediate the most common adhesion phenotype found in infected erythrocytes. Here the first crystal structure of CD36 in complex with a PfEMP1 CIDR domain is presented. Together with sequence analysis and biophysical data, it shows how parasite PfEMP1 proteins are able to diversify hugely while retaining a chemically conserved CD36 binding surface. This reveals insight into the structure and function of CD36 and shows how the parasite targets a region of CD36 that is critical for its physiological role, avoiding mutations in host receptors that would prevent parasite binding. Repetitive interspersed family proteins (RIFINs) are the most abundant variant surface antigens in P. falciparum. However, unlike the well-studied PfEMP1, the function of RIFIN remains unclear. Recently, a subset of human antibodies was identified from malaria-endemic areas that can recognise varied RIFINs. These antibodies have the unique feature of the insertion of a human receptor, LAIR1 (CD305), into the third complementarity-determining region of their heavy chain. Here, the first structure of one of these unusual LAIR1-containing antibodies is presented. It reveals that the CDR loops are mostly occluded by the insert and form a surface that positions LAIR1 for antigen binding. The variable regions of the antibody therefore no longer perform their classical role in antigen recognition. Instead they act as an adaptor between a human LAIR1 insert with antigen binding properties and the immune-modulatory antibody constant regions.